The model processor design - Kurgaev, A. F.; Grygoryev, S.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
A new sequential structure of the distributed network control unit and a methodology of model processor design, which consists in the successive building-up of the processor structure in the context of the deployment of a computational algorithm, is presented. Using this methodology, the optimal structures of a hardware for the knowledge representation and interpretation were developed and patented.